PENGARUH FAKTOR MIKROEKONOMI DAN MAKROEKONOMI TERHADAP HARGA SAHAM SEKTOR PERTANIAN - Yasir Maulana; Dikdik Harjadi; Lia Kurniasih (Bisnis-Net, 2023)
ABSTRACTThe purpose of this study is to examine the variables of microeconomic factors and macroeconomic factors on stock prices of publicly listed agricultural companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The population is 21 companies or 105 financial statement data. The sampling technique used in this study is purposive sampling. The samples taken were 16 companies or 80 financial statement data of agriculture sector companies. The variables of microeconomic and macroeconomic factors consist of Profitability, Liquidity, Solvency, Firm Size, Inflation, Economic Growth and Interest Rates. The method used in this study are panel data regression. The results showed that simultaneously Profitability, Liquidity, Solvency, Firm Size, Inflation, Economic Growth and Interest Rates have a significant effect on stock prices. And pasrtially Profitability has a positive and significant effect, Liquidity has a positive and significant effect, Solvency has a positive and significant effect, Firm Size has no positive effect, Inflation has a positive and significant effect, Economic Growth has no positive effect and Interest Rates has no negative effect on prices share.Keyword : Microeconomic, Macroeconomic, Firm Size, Interest Rate, Stock Price